Healthy lifestyle as a factor influencing the change of consumers’ trends in the Polish brewery market - Rywocki, Karol (Journal of Education, Health and Sport, 2019)
The aim of this article is to demonstrate the change in shopping trends in brewery markets in Poland, in the recent years, which is a result of growing awareness in the field of leading a healthy lifestyle by the consumers. Furthermore, the article is to present the reaction of the producers to new marketing trends through introducing new products, as well as introducing the innovations in already existing products in order to meet the needs of the consumers. Secondary sources used and analyzed by the author in the research conduced include: scientific literature, professional literature, external and internal publications of Polish brewery producers. The author has been involved in brewery market for many years as a member of managing board of two brewery factories, hence the use of his expertise based on numerous interviews with other business representatives.